High-Resolution Binding Atlas of U2AF1 Mutants Uncovers New Complexity in Splicing Alterations and Kinetics in Myeloid Malignancies - Biancon, Giulia; Joshi, Poorval; Hunck, Torben; Zimmer, Josh; Gao, Yimeng; Machyna, Martin; Botti, Valentina; Qin, Ashley; Viero, Gabriella; Neuenkirchen, Nils; Taylor, Ashley; Gbyli, Rana; et al. (Blood, 2020)
Spliceosomal gene mutations function as drivers of hematologic malignancies and other cancers with an occurrence of more than 50% in myelodysplastic syndromes and secondary acute myeloid leukemia. Hotspot mutations S34F and Q157R in the two zinc finger domains of the splicing factor U2AF1, forming with U2AF2 the U2AF complex that recognizes 3' splice site (3'SS) of U2 introns, alter exon usage in a sequence-specific manner. However, how pathological U2AF1 mutations disrupt ordered splicing, from binding to recruitment of cooperating RNA binding proteins and ultimately splicing kinetics, is still not known at the molecular level. To obtain unique insights into in vivo RNA binding mechanisms, we performed fractionated enhanced crosslinking immunoprecipitation coupled with deep RNA sequencing (freCLIP-seq) on human erythroleukemia (HEL) cells expressing wild-type (WT) or mutant (S34F, Q157R) U2AF1. Transcriptome-wide analysis of binding at single nucleotide resolution in light and heavy fractions, corresponding respectively to U2AF1 only and U2AF complex, allowed to: i) deconvolute U2AF1 signal peaking over the AG dinucleotide at the intronic end of the 3’SS region, and U2AF2 signal sitting on the adjacent polypyrimidine tract (PPT); ii) identify conformational changes in mutant U2AF1 binding with a novel peak in position -3 of the 3’SS region for S34F and in position +1 for Q157R. Alternative splicing analysis on newly collected RNA-seq data showed that less included exons present higher probability of U in position -3 for S34F and A in position +1 for Q157R, pinpointing a match with nucleotide positions affected by aberrant binding in freCLIP-seq. In both U2AF1 mutants, aberrant binding and splicing mechanisms affected genes involved in mRNA processing and transport (P-value<0.01) highlighting the involvement of U2AF1 mutations in the dysregulation of these key biological processes. We then performed a combined analysis of differential binding and aberrant splicing in U2AF1 mutants vs WT considering 4 categories: “>inclusion/>binding”, “<inclusion/<binding”, “ binding”, “>inclusion/<binding”. The first 2 categories correspond to the loss-of-function binding model suggested in literature to explain the splicing outcome of U2AF1 mutations: U2AF1 mutants bind certain splicing junctions with less affinity, leading to their exclusion. The last 2 categories represent a non-canonical gain-of-function model where increased mutant U2AF1 binding results in the impairment of the splicing machinery. Surprisingly, while Q157R mainly exhibited a loss-of-function mechanism where ineffective splicing is related to absence of binding (“<inclusion/<binding”, 51.1%), S34F mostly follows a gain-of-function mechanism affecting splicing progression by an increased, yet skewed, binding. The most represented category was, indeed, “ binding” with 123 events out of 309 (Figure 1A). Moreover, differential binding was not dependent on specific nucleotides in position -3: events characterized by increased S34F binding (Figure 1B, top), as well as events characterized by decreased S34F binding (Figure 1B, bottom), showed -3U in less included exons or -3C in more included exons. The binding analysis across the 4 categories showed that increased S34F binding was associated with reduced U2AF2 binding (Figure 1C, top) particularly in less included exons, while decreased S34F binding was associated with increased U2AF2 binding (Figure 1C, bottom) especially in more included exons. Finally, analysis of branch point and splice junction features revealed that PPT strength influences the splicing outcome with “ binding” category characterized by a weak PPT that impairs U2AF2 binding in the presence of skewed U2AF1 S34F binding (Figure 1D). Additionally, transcriptome-wide RNA kinetics analysis by TimeLapse-seq demonstrated that U2AF1 S34F and Q157R, compared to WT, globally decrease synthesis of aberrantly spliced and bound 3'SS regions. Of note, this shutdown effect was particularly evident in the downstream exons pointing towards a role of U2AF1 mutations in a widespread alteration of RNA synthesis and splicing dynamics. Collectively, these results disclose novel molecular mechanisms of pathogenic U2AF1 mutations in the context of myeloid malignancies and provide the basis for the development of effective U2AF1 directed therapeutic strategies. [Display omitted] Hunck:Boehringer Ingelheim Fonds: Other: MD Fellowship.